Performance Optimization Techniques on Point Absorber and Oscillating Water Column Wave Energy Converter: A Comprehensive Review - Aryan Manan Jariwala; Santanu Kumar Dash; Umesh Kumar Sahu; Harin M. Mohan (IEEE Access)
In recent years, harnessing renewable energy from different sources of energies readily available to us in different forms such as solar, wind, wave, hydro, tidal, biomass and hydrogen has gained popularity among researchers in different fields to counter the emissions released into the atmosphere by utilization of fossil fuels. Amongst these, wave energy is driving researchers to develop efficient systems due to its remarkably high potential providing a reliable and sustainable energy source both onshore and offshore. This paper provides a comprehensive review of the developments, various design innovations, and performance optimization techniques in the recent years of the two most common wave energy converters installed across the globe i.e., point absorber wave energy converter and oscillating water column wave energy converter. The research papers on numerical modeling, experimental analysis on laboratory scaled models, and hydrodynamic performance simulations using various softwares on both the types of wave energy converters are tabulated in a year wise format. Moreover, a list of all the installed point absorber wave energy converters and oscillating water column wave energy converters are tabulated in a year wise format along with their installed capacities, location of deployment and the country of deployment. Lastly the key advantages of both the wave energy converters are outlined below.